Electrochemical durability of magnetite and birnessite modified electrodes with potential application in water splitting - Taranu Bogdan-Ovidiu; Vlazan Paulina; Taranu Ioan; International Symposium on Analytical and Environmental Problems (27.) (2021) (Szeged) (University of Szeged Szeged, 2021)
Graphite electrodes were modified with compositions containing either Fe3O4 or δ-MnO2, and their electrochemical durability was investigated using the cyclic voltammetry method. Experimental results indicate that the most stable electrode is the one modified with the composition containing magnetite and Vulcan carbon, when exposed to electrochemical potentials in the anodic domain. Given this result and the potential values at which oxygen is evolved on the electrode, it has the prospect to find application in the water splitting domain.
Keywords: Természettudományok; Kémiai tudományok